EKSISTENSI LONTAR PRASI DI DESA TENGANAN PEGRINGSINGAN KECAMATAN MANGGIS KABUPATEN KARANGASEM - Ni Kadek Ayu Pradnyanita; Ni Made Sukerni; I Nyoman Alit Supandi (UHN IGB Sugriwa Denpasar, 2020)
The people of Bali view cultural art as an offering, as well as life balance guards, so that the art and culture development is carried out from within the family to the wider community. The art of one of the elements of universal culture includes several fields of art. One of the art that is still preserved in Bali in particular is the Lontar Prasi in the village of Tenganan Pegringsing. The Prasi-Lontar is an illustration of the puppet and gods on the Lontar leaves, one of the fine arts that includes the cultural heritage of ancestors who have high aesthetic value. The problems that will be discussed include: 1. How is the process of making Prasi Lontar in Tenganan Pegringsing village, Karangasem?. 2) How is the function of the Prasi Lontar in the life of people in Tenganan Pegringsingan village, Karangasem?. 3) The value of religion of Hinduism What is contained in the Prasi Lontar in Tenganan Pegringsingan village, Karangasem?. The theory used to analyse the problem is learning theory, used to discuss the process of making Prasi Lontar in the village of Tenganan Pegringsingan, Karangasem. Structural functional theory, which is used to discuss the function of the Prasi Lontar in the life of people in Tenganan Pegringsingan village, Karangasem. Value theory, used to discuss the value of religious education what is contained in the Prasi Lontar in the village of Tenganan Pegringsingan, Karangasem. The data collection methods used in this study are non- participant observation, interviews, documentation, and literature studies. The collected data is analyzed with qualitative descriptive analysis method with reduced steps, data presentation, conclusion withdrawal and data analysis presentation. The results of the study showed (1) the process of the establishment of the Prasi Lontar in the village of Tenganan Pegringsingan Karangasem, making Prasi Lontar has three stages, the initial stage prepared is the leaf rontal and its equipment. The creation stage is the creation of the Prasi Lontar in the form of puppet pictures and gods. The final stage is to give black using candlenut fruit. (2) The function of the Prasi Lontar in the lives of people in the village Tenganan Pegringsingan Karangasem, consists of socio-cultural function, economic function, and preservation function. (3) The value of religious education is contained in the Prasi Lontar in the village Tenganan Pegringsigan, Karangasem which is the value of Tattwa education, Susila educational value, and aesthetic education value.